No difference in the skeletal muscle angiogenic response - Gavin, Timothy Patrick; Ruster, Rebecca S.; Carrithers, John A.; Zwetsloot, Kevin A.; Kraus, Raymond M.; Evans, Christopher A.; Knapp, Deborah J.; Drew, James L.; McCartney, Jennifer S.; Garry, Joseph P.; Hickner, Robert C. (East Carolina University, 2007)
Ischaemia-induced skeletalmuscle angiogenesis is impaired in aged compared with young mice. In humans, vascular endothelial growth factor (VEGF) mRNA and protein following an acute exercise bout are lower in aged compared with young untrained men. We hypothesized that exercise-induced skeletalmuscle angiogenesiswould be attenuated in aged comparedwith young men. In eight aged (mean age: 64 years) and six young (mean age: 25 years) sedentary men, muscle biopsies were obtained from the vastus lateralis prior to (Pre), after 1 week and after 8 weeks of an aerobic exercise training program for the measurement of capillarization and VEGFmRNA. Dialysate VEGF protein collected fromthemuscle interstitial space was measured at rest and during submaximal exercise at Pre, 1 week and 8 weeks. Exercise training increased capillary contacts (CC) and capillary-to-fibre perimeter exchange index (CFPE) of type I and IIA fibres similarly in young and aged. The CC of type IIA and IIB fibres was lower in aged compared with young independent of training status. Exercise-induced interstitialVEGFprotein was lower in aged compared with young independent of training status. In untrained, greater exercise-induced interstitial VEGF protein during exercise was associated with greater type I, IIA and IIB CC. Exercise training increased VEGF mRNA similarly in young and aged. These results demonstrate that the angiogenic response to aerobic exercise training is not altered during the ageing process in humans. In addition, muscular activity-associated increases in interstitial VEGF protein may play an important role in the maintenance of skeletal muscle capillarization across the life span. Originally published Journal of Physiology, November 2007 585:1.
Keywords: Skeletal muscle; Angiogenesis; MRNA; Vascular endothelial growth factor